Detection of α Centauri at radio wavelengths: chromospheric emission and search for star–planet interaction. Issue 1 (23rd August 2018) - Trigilio, C; Umana, G; Cavallaro, F; Agliozzo, C; Leto, P; Buemi, CS; Ingallinera, A; Bufano, F; Riggi, S
ABSTRACT: At radio wavelengths, solar-type stars emit thermal free–free and gyroresonance, gyrosynchrotron, and impulsive coherent emission. Thermal free–free emission originates at layers where the optical depth is close to unit, while high brightness temperature and variable emission can be due to flares via gyrosynchrotron emission. We observed the $α \, $ Cen system with the Australian Telescope Compact Array at 2 GHz for three days and 17 GHz for one day. Both stars have been detected at 17 GHz, while only an upper limit has been obtained at low frequency despite the longer integration time. The brightness temperatures are consistent with the temperature of the upper chromosphere of the Sun. Inverting the formulae of the free–free emission, the average electron density of the plasma has been inferred. The same procedure was applied to the data in the millimetre recently acquired with ALMA. A comparison with the atmospheric solar models reveals a higher level of activity in $α \, $ Cen B rather than in $α \, $ Cen A, even if still at quiescent level. The non-detection at 2 GHz allows us to put a lower limit in the filling factor of active regions. The claimed detection of an Earth-sized planet in close orbit to $α \, $ Cen B, although doubtful, opens the opportunity to check the existence of Star–Planet Magnetic Interaction. We constructed dynamic spectra in the 1.3–2.9GHz of the two stars to search for time-variable coherent emission but obtained a null result.